Cancer risk across mammals - Vincze, Orsolya; Colchero, Fernando; Lemaître, Jean-Francois; Conde, Dalia A.; Pavard, Samuel; Bieuville, Margaux; Urrutia, Araxi O.; Ujvari, Beata; Boddy, Amy M.; Maley, Carlo C.; Thomas, Frédéric; Giraudeau, Mathieu (Nature (London), 2022)
Cancer is a ubiquitous disease of metazoans, predicted to disproportionately affect larger, long-lived organisms owing to their greater number of cell divisions, and thus increased probability of somatic mutations 1 , 2 . While elevated cancer risk with larger body size and/or longevity has been documented within species 3 – 5 , Peto’s paradox indicates the apparent lack of such an association among taxa 6 . Yet, unequivocal empirical evidence for Peto’s paradox is lacking, stemming from the difficulty of estimating cancer risk in non-model species. Here we build and analyse a database on cancer-related mortality using data on adult zoo mammals (110,148 individuals, 191 species) and map age-controlled cancer mortality to the mammalian tree of life. We demonstrate the universality and high frequency of oncogenic phenomena in mammals and reveal substantial differences in cancer mortality across major mammalian orders. We show that the phylogenetic distribution of cancer mortality is associated with diet, with carnivorous mammals (especially mammal-consuming ones) facing the highest cancer-related mortality. Moreover, we provide unequivocal evidence for the body size and longevity components of Peto’s paradox by showing that cancer mortality risk is largely independent of both body mass and adult life expectancy across species. These results highlight the key role of life-history evolution in shaping cancer resistance and provide major advancements in the quest for natural anticancer defences. An analysis of cancer mortality data for zoo mammals highlights marked differences across mammalian orders and an influence of diet, and shows that mortality risk is largely independent of body mass and life expectancy across species.